2008
DOI: 10.1590/s0103-21002008000400009
|View full text |Cite
|
Sign up to set email alerts
|

A sobrecarga da família que convive com a realidade do transtorno mental

Abstract: OBJETIVO: Conhecer a sobrecarga da família que convive com o sofrimento psíquico. MÉTODOS: Trata-se de uma pesquisa qualitativa, com abordagem hermenêutico-dialética. Os dados foram coletados por meio de entrevista semi-estruturada, com dez familiares de portadores de transtorno mental em um Centro de Atenção Psicossocial e no domicílio dos sujeitos. Os dados coletados foram agrupados em temáticas para posterior análise. RESULTADOS: Identificamos a presença de três tipos de sobrecarga: a sobrecarga financeira,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
93

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 5 publications
1
15
0
93
Order By: Relevance
“…This study also emphasized the importance of home visits as a strategy for healthcare professionals to get to know the family's reality, and subsequently provide the right orientations, allowing families to feel more confi dent and capable of acting correctly in relation to symptoms presented by the person with mental suff ering (14) . This would imply having a new care logic for people with mental disorders, one in which the family is not merely included in the care plan, but also included in the focus of care.…”
Section: [] I Came To Get Help Support and Information Here At Thmentioning
confidence: 94%
See 1 more Smart Citation
“…This study also emphasized the importance of home visits as a strategy for healthcare professionals to get to know the family's reality, and subsequently provide the right orientations, allowing families to feel more confi dent and capable of acting correctly in relation to symptoms presented by the person with mental suff ering (14) . This would imply having a new care logic for people with mental disorders, one in which the family is not merely included in the care plan, but also included in the focus of care.…”
Section: [] I Came To Get Help Support and Information Here At Thmentioning
confidence: 94%
“…A study on the burden of families who live with sufferers of mental disorders (14) , showed the importance of families in the support groups so they can get information on behaviour, symptomatology and treatment of the illness, and receive orientations on the use of psychotropic drugs and their side eff ects. This study also emphasized the importance of home visits as a strategy for healthcare professionals to get to know the family's reality, and subsequently provide the right orientations, allowing families to feel more confi dent and capable of acting correctly in relation to symptoms presented by the person with mental suff ering (14) .…”
Section: [] I Came To Get Help Support and Information Here At Thmentioning
confidence: 99%
“…Tal entendimento foi desenvolvido para definir as consequências negativas de cuidar do membro adoecido, abrangendo encargos econômicos, físicos e emocionais. 3 O adequado suporte à família é um dos pilares da Reforma Psiquiátrica, em que o trabalho de reabilitação psicossocial é entendido como um processo que visa reabilitar e desenvolver novas atitudes e comportamentos na pessoa em sofrimento mental e, também, em seus familiares. Para atender esta proposta surgiram, dentre outros serviços, os CAPS.…”
Section: Introductionunclassified
“…As ações desenvolvidas nestes serviços incluem atenção às pessoas em sofrimento mental e aos seus familiares, de forma a construir projetos de inserção social respeitando as capacidades de cada indivíduo e princípios de cidadania, potencializando maior qualidade de vida e inclusão social. [3][4] Dentre as estratégias de atenção à família, o grupo de familiares é o mais referenciado por autores e utilizado na prática em saúde mental, visto que funciona como um espaço de acolhimento à emergência da experiência de vida de cada um de seus participantes. O que requer considerar a aplicabilidade e resultados consoantes à terapia com grupos familiares e a satisfação do familiar participante.…”
Section: Introductionunclassified
“…Psychosocial Care Centers for Psychoactive Substance Users (CAPS-ad) are set up in cities with more than 70,000 inhabitants, in compliance with Ministerial Decree No 336/02, which establishes that this service is to deliver psychosocial care to people with alcohol and/or drugs dependence, with an emphasis on these clients' rehabilitation and social reinsertion (1) . Based on this care proposal, it is considered relevant to understand the organizational system of the CAPSad, as an institution's organization interferes directly in the quality of care delivery.…”
Section: Introductionmentioning
confidence: 99%